MANIFESTATION OF ETHNICITY AND VALUES: THE CASE STUDY FROM THE EASTERN LATVIA - Makarevičs, Valērijs; Iliško, Dzintra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Values has been explored in connection to a deeper understanding of human behavior. Values provide the answer to the basic existential questions, help to provide meaning in one’s life. Values are the key aspects of one’s self-esteem. They reflect diverse aspects of one’s social identity. According to a number of scientists, ethnic identity is a part of social identity. A number of studies in psychology has a focus on the connection between ethnicity and ethnic values. There are two main approaches towards the study of values can be distinguished. On the one hand, there are values that have the existential basis for the existence of people. On the other hand, the information about ethnic values can have applied aspect. The aim of this study is to identify differences in value orientation among representatives of two main linguistic groups that live in Eastern Latvia: the group of Latvian and Russian-speaking participants. The second goal is to explore the influence of religion, age and gender on the values of the research participants. The methodology used for the purpose of this study was to determine value orientation towards family, religious and friendship. The authors discovered statistically significant differences only in relation to a value of friendship. This value turned out to be the highest among the Russian-speaking group as compared to the Latvian-speaking group, as well as in the Orthodox group as compared to the group of Catholics.